Resiliensi Pesantren melalui Integrasi Nilai-nilai Islam dalam Manajemen Modern di Pondok Pesantren - Hesti Kusumaningrum; Kuncoro Rathariwibowo; Suryani Suryani; Salsabila Azahra (Intelektual)
Islamic boarding schools (pondok pesantren) not only focus on religious studies but also on social and economic empowerment. This study explores human resource management (HRM) strategies at Pondok Pesantren An Nur using a qualitative approach through observation, interviews, and document analysis. The findings indicate that the pesantren has a well-organized organizational structure, systematic work programs, and efforts to enhance the competence of ustadz through training and missionary assignments (dakwah). The management of santri is conducted through practice-based education, spiritual discipline, and skill development in the fields of dakwah and organization. Additionally, the pesantren’s relationships with the community and external institutions play a role in strengthening its social impact and program sustainability. However, challenges such as suboptimal coordination and limited resources remain. The study implies that integrating Islamic values with modern management approaches can create a more adaptive and competitive pesantren. The indicators of success include the effectiveness of work programs, improvement in the quality of ustadz and santri, and the strengthening of external networks. This research contributes by providing insights for pesantren administrators in developing innovative HRM strategies and for academics in understanding the dynamics of pesantren as educational and community empowerment institutions.